Statistical optimization for dye removal from aqueous solution by cross-linked chitosan composite / Ahmed Saud Abdulhameed, Ali H. Jawad and Abdul Karim-Talaq Mohammad - Abdulhameed, Ahmed Saud; Jawad, Ali H.; Mohammad, Abdul Karim-Talaq (Faculty of Applied Sciences, 2020)
Response surface methodology-Box–Behnken design (RSM-BBD) was employed to optimize the methyl orange (MO) dye removal efficiency from aqueous solution by cross-linked chitosantripolyphosphate/nano-titania composite (Chi-TPP/NTC). The influence of pertinent parameters, i.e. A: TiO2 loading (0- 50 %), B: dose (0.04-0.14 g), C: pH (4-10), and D: temperature (30-50 oC) on the MO removal efficiency were tested and optimized using RSM-BBD. The F-values of BBD model for MO removal efficiency was 93.4 (corresponding p-value < 0.0001). The results illustrated that the highest MO removal efficiency (87.27 %) was observed at the following conditions: TiO2 loading (50% TiO2), dose (0.09 g), pH 4.0, and temperature of 40 oC.